(untitled) (Bangladesh Journal of Agricultural Research, 2022)
The experiment was conducted to evaluate the effect of ethephon (2-chloroethyl phosphonic acid) on ripening and postharvest quality of tomato (Solanum lycopersicum). Four concentrations of ethephon viz. 250, 500, 750 and 1000 ppm were applied in the experiment for ripening of tomato under ambient conditions (22±2oC & 80±5% RH) with a control (0 ppm ethephon) in two consecutive years 2012 - 2013. The tomato fruits of ‘Udayan’ variety at breaker stage were harvested from the farmers’. The treated fruits were assessed for ripening percentage and biochemical properties such as total soluble solids (TSS) (%), titratable acidity (%), ascorbic acid content (mg/100g) and total carotenoids (mg/100g). The observations were recorded at 3, 6, 9 and 12 days after storage. The maximum TSS and total carotenoids were found in tomato treated with ethephon concentration @750 - 1000 ppm after 6 days of storage. From the experiment, it was found that ethephon can be applied @750 – 1000 ppm in breaker stage of tomato for uniform ripening within 6 days of storage at ambient temperature. The applied ethephon was estimated as 0.18 - 0.88 ppm at edible stage (6 days of storage), which was lower than the maximum residue limit (MRL) (2 ppm of ethephon) and safe for human consumption. Bangladesh J. Agril. Res. 45(3): 303-314, September 2020